A Device with a Controllable Internal Atmosphere, Independent from the Heating Furnace, for Sintering Metal Particles - M. E. Hernández–Rojas; S. L. Castañón–Alonso; S. Báez–Pimiento (Materials Research, 2024)
A device with a controllable atmosphere has been designed and fabricated to sinter metal particles in the manufacturing processes of metallic components (porous or non-porous parts). The device avoids the employment of an expensive controlled atmosphere furnace (a furnace in which it is possible to produce a vacuum or through which a constant flow of highly pure inert gas is maintained to protect the specimen). Metallic powders of pure metals or alloys with sintering temperatures (Ts) up to 1300°C and different forms and particle sizes can be used. The device consists of two chambers (an upper chamber for the atmosphere control and a lower chamber for the sintering processes) which are coupled by a sealed system composed of an O–ring and a clamp. The device is designed to be utilized with any conventional vertical electrical furnace (a furnace without the possibility of producing a vacuum inside or maintaining a constant flow of inert gas inside) and can be operated in three different ways: i) with a vacuum inside, ii) with a static atmosphere of inert gas inside, and iii) with a dynamic atmosphere of inert gas inside.